O zwykłej niechęci wobec agrapha dogmata - Szlezák, Thomas A. (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2010)
The present paper deals with eight charges that are frequently leveled against any research that focuses on the agrapha dogmata. The charges are demonstrated to be completely unfounded and, therefore, duly dismissed. In particular, it is argued here that the phrase ta legomena (so called) is by no means to be understood as ironic. Consequently, the article rejects the very common picture of Plato as some sort of dogmatist and author of a fixed philosophical system. However, Plato’s philosophy is presented as rather ‘overt’ and ‘straightforward’ in its nature. With the situation being as it is, thorough knowledge of the agrapha dogmata is shown to be an absolute prerequisite for understanding Plato’s dialogues. The paper concludes with an observation that while investigating the issue is completely warranted and does not in any way entail any devaluation of the dialogues, Aristotle’s testimony must also be taken into account.
Keywords: The theory of principles; esotericism; Plato’s indirect tradition; agrapha dogmata; Aristotle